2010
DOI: 10.2166/wst.2010.482
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the effect of cyanobacteria in the microfiltration of secondary effluent

Abstract: Cyanobacterial blooms in the lagoons of sewage treatment plants can severely impact the performance of membrane plants treating the effluent. This paper investigates the impact of Microcystis aeruginosa in a secondary effluent on the microfiltration filterability and cleaning of the membrane. Alum coagulation and dissolved air flotation (DAF) were investigated to remove the algae and so enhance the volume of effluent processed, and their influence on reversible and irreversible fouling. Degree of fouling due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…AOM has been demonstrated to cause severe fouling for low-pressure polymeric [5][6][7][8] and ceramic membranes [9,10] as it contains a high proportion of high molecular weight (MW) biopolymers such as polysaccharides and proteinaceous substances which have been identified as the most problematic foulants for the membranes. Moreover, the blooms can lead to the release of harmful algal metabolites including toxins into the drinking water, posing a threat to human health [11].…”
Section: Introductionmentioning
confidence: 99%
“…AOM has been demonstrated to cause severe fouling for low-pressure polymeric [5][6][7][8] and ceramic membranes [9,10] as it contains a high proportion of high molecular weight (MW) biopolymers such as polysaccharides and proteinaceous substances which have been identified as the most problematic foulants for the membranes. Moreover, the blooms can lead to the release of harmful algal metabolites including toxins into the drinking water, posing a threat to human health [11].…”
Section: Introductionmentioning
confidence: 99%
“…AOM comprises mainly high molecular weight (MW) organics such as protein-like and polysaccharide-like substances [5] which can cause severe membrane fouling and lead to decrease in membrane permeability [3,4]. It has been demonstrated that the presence of AOM in addition to the effluent organic matter in secondary effluent can further reduce the efficiency of LPM filtration [6,7], thus increasing the operating cost. However, Lee and Walker [8] reported that hydrophobic polysulfone UF membrane could remove 91% of microcystin-LR whereas hydrophilic CA membranes adsorbed little or no microcystin-LR.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the fouling potential of the AOM from M. aeruginosa is greatest at the stationary phase of growth [4,6,9]. Goh et al [6] reported that the extracellular organic matter caused greater fouling than the cells during stationary phase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations